2013
DOI: 10.1002/ange.201300560
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Crystalline Polymer and Block Copolymer Domain Alignment Controlled by Free‐Surface Segregation

Abstract: The surface effects and anchoring of liquid crystals (LCs) have long been significant concerns for material chemists and physicists.[1] The surface alignment of LCs by mechanical rubbing [2] is a widely recognized phenomenon and of particular significance in technological applications for display device fabrication.[3] Surface molecular orientations [4] and topographical grooves and undulations [5] of the substrate provide LC alignment effects. Furthermore, in the past two decades, the photoalignment of LCs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…1 , right). This approach was inspired by our recent results showing that the surface coverage on the free surface of photoresponsive azobenzene side chain LC polymer films leads to a homoeotropic to planar orientational change in the mesogenic groups across the entire film 21 22 . This pre-oriented state leads to an effective in-plane photoalignment using LPL irradiation.…”
mentioning
confidence: 99%
“…1 , right). This approach was inspired by our recent results showing that the surface coverage on the free surface of photoresponsive azobenzene side chain LC polymer films leads to a homoeotropic to planar orientational change in the mesogenic groups across the entire film 21 22 . This pre-oriented state leads to an effective in-plane photoalignment using LPL irradiation.…”
mentioning
confidence: 99%
“…The θ gly values of a mixture of PAz and PCPBz (5:95 by weight) after annealing at 90 °C for 10 min before and after UV irradiation were 99.2 ± 1.6° and 89.4 ± 1.6° at 25 °C, which agree well with those of the pure PAz film (Table 1 ). These results indicate that annealing selectively segregates the PAz component to the free surface 41 43 .…”
Section: Resultsmentioning
confidence: 80%
“…Such a surface is called the command layer 45,52,63 . Recent investigations have revealed that a photoactive command layer can be placed at the free surface in SCLCP films [41][42][43][44][45][46][47] . Similarly, the present work offers another command layer scenario where large www.nature.com/scientificreports/ molecular amplification is reflected in macroscopic surface morphing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuhara et al 127 demonstrated that a PS-b-PAz film with vertically aligned PS MPS cylinders can be converted to a planar orientation by mixing in a small amount of PBMA-b-PAz and then annealing (case f in Figure 4). Coverage of the segregated PBMA-b-PAz at the free surface of PS-bPAz is responsible for this orientational inversion.…”
Section: Photoalignment Of Block Copolymer Films Via Free Surface Segmentioning
confidence: 99%